2020
DOI: 10.1111/dme.14396
|View full text |Cite
|
Sign up to set email alerts
|

Childhood food insecurity and incident diabetes: A longitudinal cohort study of 34 042 children in Ontario, Canada

Abstract: Aim: To examine the association between childhood food insecurity and incident diabetes. Methods: Using health administrative databases linked to the Canadian Community Health Survey, we conducted a population-based cohort study of children aged <18 years from Ontario, Canada. Children without diabetes who had a household response to the Canadian Community Health Survey Household Food Security Survey Module were followed for a median of 9.5 years for incident diabetes. Multivariable Cox proportional hazards mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…At the same time, up to 10% of households in the United Kingdom are affected by moderate or severe food insecurity, a risk factor for poor nutrition and obesity in children, and diabetes prevalence in adults. Reassuringly, food insecurity is not reported to be associated with incident diabetes in children, as reported in this issue, 10 with clinical and socio‐economic risks accounting for new onset diabetes. I was again very fortunate to be able to discuss this paper with the authors and the podcast is available to listen to at the link above.…”
mentioning
confidence: 62%
“…At the same time, up to 10% of households in the United Kingdom are affected by moderate or severe food insecurity, a risk factor for poor nutrition and obesity in children, and diabetes prevalence in adults. Reassuringly, food insecurity is not reported to be associated with incident diabetes in children, as reported in this issue, 10 with clinical and socio‐economic risks accounting for new onset diabetes. I was again very fortunate to be able to discuss this paper with the authors and the podcast is available to listen to at the link above.…”
mentioning
confidence: 62%
“…Our child cohort was built using previously described methods [ 18 ]. In brief, we included children in three ways.…”
Section: Methodsmentioning
confidence: 99%
“…Given the small number of severely food insecure children in our cohort (n = 1079), we a-priori grouped both moderately and severely food insecure children into one “food insecure” category. A similar approach has been used in previous research studies on food insecurity, including our recently published report [ 18 , 19 ]. We defined unexposed children as those who were food secure as per the HFSSM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that adults in families with food insecure households are more susceptible to heart disease, diabetes, hypertension, increased inflammation and obesity (29)(30)(31). Moreover, children in families experiencing food insecure are more prone to psychosocial, cognitive and behavioral problems as well as a reduction in the intake of important nutrients and developmental deficiencies (32)(33)(34)(35).…”
Section: Food Insecurity During Covid-crisismentioning
confidence: 99%